2007
DOI: 10.5713/ajas.2007.359
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Scrotal Circumference and Semen Characteristics of Black Bedouin and Black Bedouin-Damascus Crossbred Bucks

Abstract: The objective of this study was to evaluate monthly variation in semen characteristics in Black Bedouin and Black Bedouin×Damascus crossbred bucks. Twenty one Black Bedouin Goat bucks (BG) and 20 F 1 Black Bedouin×Damascus crossbred goat bucks (CB) were used in the study. Animals were 2 to 5 years old at the beginning of the study. Body weight (BW), body condition score (BCS), scrotal circumference (SC) and semen samples were evaluated monthly for all bucks. Body weight, BCS and SC differed according to month … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…The percentage of spermatozoa high mitochondrial membrane potential of non-washed and washed semen samples extended with Bioxcell ® were significantly lower (P<0.05) than the non-washed and washed semen samples extended with Triladyl ® . There was a high percentage of abnormal spermatozoa in the current study, which concur with what [27] and [28] reported during spring season.…”
Section: Discussionsupporting
confidence: 91%
“…The percentage of spermatozoa high mitochondrial membrane potential of non-washed and washed semen samples extended with Bioxcell ® were significantly lower (P<0.05) than the non-washed and washed semen samples extended with Triladyl ® . There was a high percentage of abnormal spermatozoa in the current study, which concur with what [27] and [28] reported during spring season.…”
Section: Discussionsupporting
confidence: 91%
“…Both South African unimproved indigenous and Tankwa goats used in this study were lighter when compared to Black Bedouin and Black Bedouin X Damascus males (63.2±5.0 and 60.4±7.1 kg, respectively) used in the previous study (Mellado et al, 2012). That might be due to breed differences and feeding regime as in Mellado et al (2012) study a commercial diet was used to feed the experimental animals (Kridli et al, 2007), whereas in the current study they were grazing on natural pasture. However, some of the body measurements of South African unimproved indigenous and Tankwa goats' evaluated in the current study fall within the literature estimates from tropical and subtropical breeds (Nsoso et al, 2004).…”
Section: Discussionmentioning
confidence: 90%
“…The age of mature males at the Agricultural Research Council aligns well with Pezzanite et al (2015), who indicated that the optimal breeding age of male goats ranges from 6 months to 4 years. Moreover, the age range of the goats at Agricultural Research Council seems to be a standard range that the intensive famers or research institutes are keeping (Kridli et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Practitioners used to conduct a general physical examination, scrotal circumference estimation and semen analysis to determine the reproductive soundness in male farm animals (Karaca et al., 2016; Kridli et al., 2007). Recently, the application of pulsed wave Doppler ultrasonography has become a useful noninvasive practice to assess the reproductive performance in male animals through the analysis of the blood flow dynamics within the testicular artery (Hedia & El‐Belely, 2021; Samir et al., 2015; Velasco & Ruiz, 2021).…”
Section: Introductionmentioning
confidence: 99%